Molecularly imprinted electrochemical sensor, preparation method and application thereof
Patent Information
- Application Number
- CN202611246826.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-30
AI Technical Summary
其中,高效液相色谱法、液相色谱-串联质谱法、毛细管电泳法等仪器分析方法,凭借其高灵敏度与强特异性,是目前动物源食品中头孢氨苄定量检测的权威手段,但这类方法普遍存在设备购置与维护成本高、样品前处理步骤繁琐、检测周期长、依赖专业操作人员等问题,难以满足现场快速筛查的需求
本发明提供了一种分子印迹电化学传感器,包括:电极基底;覆盖于所述电极表面的复合材料层;以及设置于所述复合材料层表面的分子印迹聚合物膜;所述复合材料层包括Ti3C2MXene/MWCNTs-COOH/UIO-66-NH2复合材料。本发明采用MWCNTs-COOH和UIO-66-NH2与Ti3C2MXene进行复合,可解决单一Ti3C2Tx纳米片在制备及应用过程中发生重新团聚堆叠现象的问题,复合材料各组分间产生协同作用,有助于改善导电性,提升响应电流。本发明采用该复合材料制备分子印迹电化学传感器,可使得分子印迹聚合物对目标待测物具有较强的选择性结合能力,尤其可增强分子印迹聚合物对β-内酰胺类抗生素的的选择性结合能力,并且,能够减少非目标物质的干扰与非特异性吸附,有利于提升检测体系的选择性与可靠性。
Smart Images

Figure CN123008932A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sensor technology, specifically relating to a molecularly imprinted electrochemical sensor, its preparation method, and its application. Background Technology
[0002] Cephalexin is a first-generation oral cephalosporin antibiotic, characterized by its broad antibacterial spectrum, good oral absorption, and stability against acids and penicillinase. Cephalexin is a white or milky-yellow crystalline powder with a slight odor, slightly soluble in water, and insoluble in ethanol, chloroform, or ether. Its aqueous solution has a pH of 3.5-5.5 and is relatively chemically stable, but it is easily hydrolyzed and inactivated in high-temperature, strongly acidic, or strongly alkaline environments. The mechanism of action of cephalexin lies in its β-lactam structure, which binds to bacterial penicillin-binding proteins (PBPs), inhibiting bacterial cell wall synthesis. This leads to bacterial rupture and death due to cell wall defects and osmotic pressure imbalance, thereby exerting a bactericidal effect. Based on these characteristics, cephalexin is widely used in livestock farming to treat respiratory, urinary tract, and skin / soft tissue infections in poultry. However, in the prevention and treatment of animal diseases or as a feed additive, misuse, abuse, and failure to adhere to withdrawal periods have resulted in excessive cephalexin residues in meat, eggs, and milk. Long-term consumption of food containing excessive levels of cephalexin can cause various toxic side effects, including allergic reactions, intestinal flora imbalance, and liver and kidney damage. It may also induce antibiotic resistance in bacteria, posing a potential threat to public health and safety.
[0003] Currently, the mainstream detection technologies for cephalosporin antibiotic residues can be divided into two main categories: large-scale instrumental analysis methods and rapid detection methods. Among these, instrumental analysis methods such as high-performance liquid chromatography (HPLC), liquid chromatography-tandem mass spectrometry (LC-MS / MS), and capillary electrophoresis, due to their high sensitivity and strong specificity, are the authoritative means for the quantitative detection of cefalexin in animal-derived foods. However, these methods generally suffer from high equipment purchase and maintenance costs, cumbersome sample pretreatment steps, long detection cycles, and reliance on specialized operators, making them difficult to meet the needs of rapid on-site screening. Microbiological detection methods, as traditional qualitative methods, are low-cost and have low operational barriers, but their detection cycles are long, results are easily affected by environmental factors, and repeatability is poor. Furthermore, they can only perform preliminary screening and cannot achieve precise quantification. In addition, novel detection technologies such as photoelectrochemical detection and fluorescence immunoassay have also been used for cefalexin detection. However, photoelectrochemical methods suffer from complex material preparation and performance susceptibility to environmental influences, while immunoassay technologies based on aptamers or antibodies face limitations such as high development costs of recognition elements and insufficient stability. Therefore, developing a simple, low-cost, rapid-response, and stable method for detecting cephalexin residues is of great significance for ensuring the safety of animal-derived food and public health. Summary of the Invention
[0004] To overcome at least one of the problems existing in the prior art, one objective of the present invention is to provide a molecularly imprinted electrochemical sensor. A second objective of the present invention is to provide a method for preparing the aforementioned molecularly imprinted electrochemical sensor. A third objective of the present invention is to provide applications of the aforementioned molecularly imprinted electrochemical sensor. A fourth objective of the present invention is to provide a method for detecting β-lactam antibiotics.
[0005] Among the many MXene materials, Ti3C2T x It is the most studied type. Its conductivity reaches metallic levels, approximately 6000-8000 S / cm, while also exhibiting good hydrophilicity and abundant functional groups (such as -O, -OH, -F) on its surface. In electrochemical sensors, Ti3C2T... x It can not only act as a charge transfer promoter, but also directly participate in electrocatalytic reactions, amplifying the detection signal. However, Ti3C2T x During the preparation and application of nanosheets, they are prone to re-aggregation and stacking due to van der Waals forces. This leads to a decrease in their effective specific surface area and the number of active sites. Therefore, it is usually necessary to suppress their self-stacking behavior by combining them with other nanomaterials. This invention innovatively proposes a Ti3C2MXene / MWCNTs-COOH / UiO-66-NH2 composite material. Compared with pure Ti3C2MXene, the components of this composite material exhibit synergistic effects, which help improve conductivity and increase response current.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A first aspect of the present invention provides a molecularly imprinted electrochemical sensor, comprising: an electrode substrate; a composite material layer covering the surface of the electrode substrate; and a molecularly imprinted polymer film disposed on the surface of the composite material layer; The composite material layer comprises a Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material.
[0007] Preferably, the molecularly imprinted polymer film contains imprinted cavities that match the structure of β-lactam antibiotics.
[0008] More preferably, the β-lactam antibiotics include penicillin antibiotics, cephalosporin antibiotics, or carbapenem antibiotics.
[0009] More preferably, the cephalosporin antibiotics include cephalexin, cefadroxil, cefadroxil, cefazolin, cefotaxime, cefepime, cefuroxime, cefuroxime, cefuroxime, cefmandole, or cefotiam.
[0010] Preferably, the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material is a composite of Ti3C2MXene, MWCNTs-COOH and UIO-66-NH2.
[0011] Ti3C2MXene is a two-dimensional transition metal carbide material, which is prepared by selectively etching away the Al layer from the MAX phase Ti3AlC2. It has a layered two-dimensional lamellar structure, with a common particle size range of approximately 100-300 nm in lateral size and 1-5 layers in thickness.
[0012] MWCNTs-COOH are carboxylated multi-walled carbon nanotubes.
[0013] UIO-66-NH2 is an amino-functionalized zirconium oxide-based metal-organic framework, a metal-organic framework material constructed based on zirconium clusters and 2-aminoterephthalic acid ligands.
[0014] Preferably, the preparation method of the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material includes the following steps: The Ti3C2MXene / MWCNTs-COOH composite material, ZrCl4, and 2-aminoterephthalic acid were subjected to a solvothermal reaction to obtain the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material.
[0015] More preferably, the temperature of the solvothermal reaction is 110-130 °C.
[0016] More preferably, the temperature of the solvothermal reaction is any value or a range formed by any two of the following: 110, 112, 114, 116, 118, 120, 122, 124, 126, 128, and 130 °C.
[0017] More preferably, the reaction time of the solvothermal reaction is 14-18 h.
[0018] More preferably, the mass ratio of the Ti3C2MXene / MWCNTs-COOH composite material to ZrCl4 is (1-4):1.
[0019] More preferably, the mass ratio of the Ti3C2MXene / MWCNTs-COOH composite material to ZrCl4 is any value or any two values within the range of 1.0:1, 1.5:1, 2.0:1, 2.5:1, 3.0:1, 3.5:1, and 4.0:1.
[0020] More preferably, the mass ratio of 2-aminoterephthalic acid to ZrCl4 is (0.6-1.5):1.
[0021] More preferably, the mass ratio of 2-aminoterephthalic acid to ZrCl4 is any value or any two values within the range of 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, and 1.5:1.
[0022] More preferably, the solvothermal reaction is carried out in N,N-dimethylformamide (DMF).
[0023] More preferably, the process specifically includes the following steps: mixing Ti3C2MXene / MWCNTs-COOH composite material, ZrCl4 and 2-aminoterephthalic acid in a solvent, then adding acetic acid and carrying out a solubilothermic reaction to obtain the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material.
[0024] More preferably, the method further includes the following steps: after the heat of solution reaction, the powder product is collected, washed with methanol, and dried to obtain the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material. The second aspect of this invention provides a method for preparing the molecularly imprinted electrochemical sensor described in the first aspect, comprising the following steps: A solution containing the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material was coated onto an electrode substrate. After removing the solvent, an electrode covered with the composite material layer was obtained. A molecularly imprinted polymer film was prepared on the surface of the electrode covered with the composite material layer to obtain the molecularly imprinted electrochemical sensor.
[0025] Preferably, the solvent of the solution containing the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material is DMF.
[0026] Preferably, the method for removing the solvent is drying.
[0027] Preferably, the preparation process of the molecularly imprinted polymer membrane specifically includes: preparing an electrolyte with functional monomers and template molecules, electropolymerizing the electrode covering the composite material layer in the electrolyte to obtain a polymer membrane with a molecularly imprinted template, and obtaining the molecularly imprinted electrochemical sensor after eluting the template molecules.
[0028] The third aspect of this invention provides the application of the molecularly imprinted electrochemical sensor described in the first aspect in the detection of β-lactam antibiotics.
[0029] Preferably, the β-lactam antibiotics include penicillin antibiotics, cephalosporin antibiotics, or carbapenem antibiotics.
[0030] Preferably, it is used to detect β-lactam antibiotics in milk.
[0031] The fourth aspect of the present invention provides a method for detecting β-lactam antibiotics, using the molecularly imprinted electrochemical sensor described in the first aspect, comprising the following steps: placing the molecularly imprinted electrochemical sensor in a test solution for adsorption, and detecting the current response signal of the sensor using an electrochemical method.
[0032] Preferably, the method further includes the following steps: establishing a sensor response signal and a standard curve of β-lactam antibiotics using a standard solution of β-lactam antibiotics, and calculating the content of the standard solution of β-lactam antibiotics in the sample to be tested based on the current response signal.
[0033] The beneficial effects of this invention are: This invention provides a molecularly imprinted electrochemical sensor, comprising: an electrode substrate; a composite material layer covering the electrode surface; and a molecularly imprinted polymer film disposed on the surface of the composite material layer; the composite material layer comprises a Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material. This invention utilizes the composite of MWCNTs-COOH and UIO-66-NH2 with Ti3C2MXene to address the limitations of a single Ti3C2T... x The problem of re-aggregation and stacking of nanosheets during preparation and application is addressed by the synergistic effect among the components of the composite material, which helps improve conductivity and increase response current. This invention utilizes this composite material to prepare a molecularly imprinted electrochemical sensor, enabling the molecularly imprinted polymer to exhibit strong selective binding ability to target analytes, particularly enhancing its selective binding ability to β-lactam antibiotics. Furthermore, it reduces interference and non-specific adsorption of non-target substances, thus improving the selectivity and reliability of the detection system.
[0034] This invention also provides a method for retrieving β-lactam antibiotics. The prepared modified composite electrode is placed in the test solution for incubation. If the solution contains β-lactam antibiotics, the substance will be specifically adsorbed by the sensor. Then, the differential pulse voltammetry is used to carry out electrochemical testing. The response current signal of the system will show a significant decrease compared with the blank system. Attached Figure Description
[0035] Figure 1 This describes the fabrication process of a molecularly imprinted electrochemical sensor.
[0036] Figure 2Cyclic voltammetry diagrams of modified electrodes with different materials in potassium ferricyanide.
[0037] Figure 3 The cyclic voltammetry plots of the MIP and NIP composites in potassium ferricyanide are shown.
[0038] Figure 4 Impedance diagrams for different modified electrodes in potassium ferricyanide.
[0039] Figure 5 Impedance plots of MIP and NIP of the composite material in potassium ferricyanide.
[0040] Figure 6 The prepared Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 molecularly imprinted electrochemical sensor was incubated for 15 min in cephalexin solutions of different concentrations before being placed in a solution containing 5 mM [Fe(CN)6]. 3- / 4- Square wave voltammetry experiments were conducted in solutions of 0.1 M KCl at concentrations of 10 nM, 50 nM, 100 nM, 500 nM, 800 nM, 1 μM, 5 μM, 10 μM, 50 μM, and 100 μM.
[0041] Figure 7 for Figure 6 The graph shows the relationship between the current value and the logarithm of the cefalexin concentration.
[0042] Figure 8 The prepared MWCNTs-COOH / UIO-66-NH2 molecularly imprinted electrochemical sensor was incubated for 15 min in cephalexin solutions of different concentrations before being placed in a solution containing 5 mM [Fe(CN)6]. 3- / 4- Square wave voltammetry experiments were conducted in solutions of 0.1 M KCl at concentrations of 500 nM, 1 μM, 5 μM, and 10 μM.
[0043] Figure 9 for Figure 8 The graph shows the relationship between the current value and the logarithm of the cephalexin concentration.
[0044] Figure 10 The prepared Ti3C2MXene / MWCNTs-COOH molecularly imprinted electrochemical sensor was incubated for 15 min in cephalexin solutions of different concentrations before being placed in a solution containing 5 mM [Fe(CN)6]. 3- / 4- Square wave voltammetry experiments were performed in solutions of 0.1 M KCl at concentrations of 500 nM, 1 μM, 5 μM, 10 μM, and 50 μM.
[0045] Figure 11 for Figure 10 The graph shows the relationship between the current value and the logarithm of the cephalexin concentration. Detailed Implementation
[0046] The present invention will be further described in detail below through specific embodiments. Unless otherwise specified, the raw materials used in the following embodiments can be obtained from conventional commercial channels or prepared and isolated through simple synthesis; unless otherwise specified, the processes employed are conventional processes in the art.
[0047] Example 1 This embodiment provides a molecularly imprinted electrochemical sensor for rapid detection of cephalexin. This electrochemical sensor is prepared by modifying a GCE with a Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material. The Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 / GCE is formed by electropolymerization using o-phenylenediamine as the functional monomer and cephalexin as the template molecule. The specific preparation steps are as follows: (1) Preparation of Ti3C2MXene by etching method. Ti3C2MXene nanosheets were synthesized by selective etching of the Ti3AlC2 aluminum layer. 2.0 g of Ti3AlC2 powder was weighed and placed in a 100 mL polytetrafluoroethylene liner. 20 mL of 49% hydrofluoric acid was slowly added dropwise under stirring. The mixture was stirred continuously at room temperature for 48 h to ensure that the aluminum layer of Ti3AlC2 was fully etched. After centrifugation of the black suspension, the precipitate was collected and washed with ultrapure water until the pH of the supernatant was close to 7.0. Finally, the sample was placed in a freeze dryer overnight and ground to obtain Ti3C2MXene powder.
[0048] (2) Preparation of Ti3C2MXene / MWCNTs-COOH by ultrasonic stirring. 0.6 g Ti3C2MXene was dispersed in 50-70 mL of deionized water to obtain solution A, which was then ultrasonicated until uniformly dispersed. 0.2 g MWCNTs-COOH was dispersed in 20 mL of deionized DMF to obtain solution B, which was then ultrasonicated until uniformly dispersed. Solution A was poured into solution B and ultrasonic stirring was continued for 2 h. The product was filtered and vacuum dried to obtain Ti3C2MXene / MWCNTs-COOH powder.
[0049] (3) Preparation of UIO-66-NH2 by hydrothermal method. 50 mg of ZrCl4 and 50 mg of diaminoterephthalic acid (2-NH2-BDC) were dissolved in 20 mL of DMF and continuously stirred magnetically for 30 min. Then, 10 mL of acetic acid was added to the solution. After stirring evenly, the mixture was transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene and heated at 120 °C for 16 h. After the reaction was completed, the precipitated solid powder was collected, washed several times with methanol, and finally dried at 60 °C overnight to obtain UIO-66-NH2 powder.
[0050] (4) Preparation of Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 by hydrothermal method. 50 mg ZrCl4 and 50 mg diaminoterephthalic acid (2-NH2-BDC) were dissolved in 10-30 ml DMF by vigorous stirring, and named solution A. Then, 100 mg of Ti3C2MXene / MWCNTs-COOH was ultrasonically dispersed in 20 mL DMF for 30 min, named solution B. Solution A was added to solution B to obtain solution C. Then, 10 mL of acetic acid was added to solution C under continuous mechanical stirring for 30 min. Next, the four suspensions were transferred to a polytetrafluoroethylene-lined stainless steel autoclave and heated at 120 °C for 16 h. After that, the powder was separated, washed several times with methanol, and dried overnight at 60 °C.
[0051] (5) Before modifying the electrode, the glassy carbon electrode is first pretreated by thoroughly polishing the bare GCE with 0.3 μm and 0.05 μm alumina slurry until the surface is like a mirror. The electrode is then cleaned with ethanol and ultrapure water alternately for 30 s and the electrode surface is dried with high-purity nitrogen.
[0052] (6) The Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material obtained in step (4) is dispersed in DMF and ultrasonically dispersed evenly to obtain a stable suspension. Then, the obtained suspension is drop-coated onto the surface of the GCE electrode treated in step (6) and dried in an oven at 60 ℃ to obtain the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 / GCE electrode.
[0053] (7) The electrode obtained in (6) was placed in a phosphate buffer solution (pH=6.5) containing cephalexin and o-phenylenediamine, wherein the molar ratio of cephalexin to o-phenylenediamine was 1:3. Electropolymerization was carried out by cyclic voltammetry with a potential range of -0.2 to 1 V and a scan rate of 50 mV / s. The number of cycles was 5, 10, 15, 20, and 25, respectively, to obtain the MIP / Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 / GCE electrode. After drying, the next step was carried out.
[0054] (8) The electrode obtained in step (7) is placed in a methanol:acetic acid solution for a certain period of time to elute and remove cephalexin molecules. Then it is washed with deionized water to obtain the eluted MIP / Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 / GCE electrode. It is then dried for the next step.
[0055] Non-molecularly imprinted polymers (NIPs) sensors were prepared under the same conditions, except that no template molecules were added during the fabrication process, resulting in NIPs / Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 / GCE electrodes.
[0056] The electrode obtained from the previous elution step was incubated in a 1 mM cefquinoxime solution for 15 min. The preparation conditions for non-molecularly imprinted electrodes were based on the optimal experimental conditions selected for molecularly imprinted electrodes.
[0057] Comparative Example 1 This comparative example provides a molecularly imprinted electrochemical sensor, which is prepared by modifying GCE with a MWCNTs-COOH / UIO-66-NH2 composite material. The MWCNTs-COOH / UIO-66-NH2 / GCE is formed by electropolymerization using o-phenylenediamine as the functional monomer and cephalexin as the template molecule. The specific preparation steps differ from those in the examples in the following ways: MWCNTs-COOH / UIO-66-NH2 was prepared by ultrasonic stirring. 10 mg UIO-66-NH2 and 50 mg MWCNTs-COOH were dispersed in 10 mL of deionized water and ultrasonicated until uniformly dispersed. The product was filtered and vacuum dried to obtain MWCNTs-COOH / UIO-66-NH2 powder.
[0058] The MWCNTs-COOH / UIO-66-NH2 composite material was dispersed in DMF and ultrasonically dispersed to obtain a stable suspension. The resulting suspension was then drop-coated onto the surface of the treated GCE electrode.
[0059] Comparative Example 2 This comparative example provides a molecularly imprinted electrochemical sensor, which is prepared by modifying GCE with a Ti3C2MXene / MWCNTs-COOH composite material. The Ti3C2MXene / MWCNTs-COOH / GCE is formed by electropolymerization using o-phenylenediamine as the functional monomer and cephalexin as the template molecule. The specific preparation steps differ from those in the examples in the following ways: The Ti3C2MXene / MWCNTs-COOH composite material from step (2) was directly dispersed in DMF and ultrasonically dispersed to obtain a stable suspension. The resulting suspension was then drop-coated onto the surface of the treated GCE electrode.
[0060] Comparative Example 3 This comparative example provides a molecularly imprinted electrochemical sensor, which is a GCE modified with Ti3C2MXene material.
[0061] Comparative Example 4 This comparative example provides a molecularly imprinted electrochemical sensor, which is a GCE modified with UIO-66-NH2 material.
[0062] Sensor performance testing Figure 2 , Figure 3 Cyclic voltammetry experiments were conducted using the different modified electrodes, as well as MIP and NIP, in a voltage range of -0.2 V to 0.6 V, with a 5 mM [Fe(CN)6] solution as the detection solution. 3- / 4- And 0.1 M KCl. The obtained data were plotted to compare the current magnitudes between different modified electrodes. It can be seen from the figure that when the MIP / Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 / GCE electrode was electropolymerized by cyclic voltammetry in the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 / GCE electrode, the current value decreased, and when this electrode was placed in the eluent for elution, the current value increased again.
[0063] from Figure 4 , Figure 5As can be seen from the EIS tests performed on the composite materials of Ti3C2MXene, UIO-66-NH2, Ti3C2MXene / MWCNTs-COOH, Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2, the polymerized Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2, the eluted Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2, and the re-incubated Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2, the final composite material exhibits the lowest resistance, while the polymerized electrode exhibits the highest resistance. The diameter of the semicircle in the high-frequency region directly corresponds to the interfacial charge transfer resistance Rct; a smaller semicircle indicates superior charge transfer kinetics and stronger interfacial conductivity.
[0064] The electrode eluted with the elution buffer in Example 1 was incubated in cephalexin solution for 15 min. The incubated electrode was then subjected to differential pulse voltammetry (DPV) experiments using a 5 mM [Fe(CN)6] electrolyte. 3- / 4- and 0.1 MKCl solution.
[0065] Figure 6 The eluted MIP / Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 / GCE electrode was incubated for 15 min in cefquinoxime solutions of different concentrations (10 nM, 50 nM, 100 nM, 500 nM, 1 μM, 5 μM, 10 μM) before being subjected to differential pulse voltammetry (DPV) testing. The voltage range was -0.2 V to 0.6 V, and the test solution was 5 mM [Fe(CN)6]. 3- / 4- And 0.1 M KCl.
[0066] Figure 7 The graph shows the relationship between the peak current obtained by differential pulse voltammetry (DPV) and the logarithm of the concentration of the eluted MIP / Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 / GCE electrode after incubating it in cephalexin solutions of different concentrations for 15 min.
[0067] Figure 8The eluted MIP / MWCNTs-COOH / UIO-66-NH2 / GCE electrode was incubated for 15 min in cefquinoxime solutions of different concentrations (500 nM, 1 μM, 5 μM, and 10 μM) before being subjected to differential pulse voltammetry (DPV) testing. The voltage range was -0.2 V to 0.6 V, and the test solution was 5 mM [Fe(CN)6]. 3- / 4- And 0.1M KCl.
[0068] Figure 9 The graph shows the relationship between the peak current obtained by differential pulse voltammetry (DPV) and the logarithm of the concentration of the eluted MIP / MWCNTs-COOH / UIO-66-NH2 / GCE electrode after incubating it in cephalexin solutions of different concentrations for 15 min. It can be seen that the linearity of MIP / MWCNTs-COOH / UIO-66-NH2 / GCE is not as good as that of MIP / Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 / GCE.
[0069] Figure 10 The eluted MIP / Ti3C2MXene / MWCNTs-COOH / GCE electrode was incubated for 15 min in cefquinoxime solutions of different concentrations (500 nM; 1 μM; 5 μM; 10 μM; 50 μM) before being subjected to differential pulse voltammetry (DPV) testing within a voltage range of -0.2 V to 0.6 V. The test solution was 5 mM [Fe(CN)6]. 3- / 4- And 0.1 M KCl.
[0070] Figure 11 The graph shows the relationship between the peak current obtained by differential pulse voltammetry (DPV) and the logarithm of the concentration of the eluted MIP / Ti3C2MXene / MWCNTs-COOH / GCE electrode after incubating it in cephalexin solutions of different concentrations for 15 min. It can be seen that MIP / Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 / GCE has the best linearity and a wider range.
[0071] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A molecularly imprinted electrochemical sensor, characterized in that, include: Electrode substrate; A composite material layer covering the surface of the electrode substrate; And a molecularly imprinted polymer film disposed on the surface of the composite material layer; The composite material layer comprises a Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material.
2. The molecularly imprinted electrochemical sensor according to claim 1, characterized in that, The molecularly imprinted polymer membrane contains imprinted cavities that match the structure of β-lactam antibiotics.
3. The molecularly imprinted electrochemical sensor according to claim 1, characterized in that, The preparation method of the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material includes the following steps: The Ti3C2MXene / MWCNTs-COOH composite material, ZrCl4, and 2-aminoterephthalic acid were subjected to a solvothermal reaction to obtain the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material.
4. The molecularly imprinted electrochemical sensor according to claim 3, characterized in that, The temperature of the solvothermal reaction is 110-130 ℃.
5. The molecularly imprinted electrochemical sensor according to claim 3, characterized in that, The mass ratio of the Ti3C2MXene / MWCNTs-COOH composite material to ZrCl4 is (1-4):
1.
6. The method for preparing the molecularly imprinted electrochemical sensor according to any one of claims 1-5, characterized in that, Includes the following steps: A solution containing the Ti3C2MXene / MWCNTs-COOH / UIO-66-NH2 composite material was coated onto an electrode substrate. After removing the solvent, an electrode covered with the composite material layer was obtained. A molecularly imprinted polymer film was prepared on the surface of the electrode covered with the composite material layer to obtain the molecularly imprinted electrochemical sensor.
7. The method for preparing a molecularly imprinted electrochemical sensor according to any one of claims 6, characterized in that, The specific preparation process of the molecularly imprinted polymer membrane includes: preparing an electrolyte using functional monomers and template molecules; electropolymerizing the electrode covering the composite material layer in the electrolyte to obtain a polymer membrane with a molecularly imprinted template; and obtaining the molecularly imprinted electrochemical sensor after eluting the template molecules.
8. The use of the molecularly imprinted electrochemical sensor according to any one of claims 1-5 in the detection of β-lactam antibiotics.
9. The application according to claim 8, characterized in that, The β-lactam antibiotics include penicillin antibiotics, cephalosporin antibiotics, or carbapenem antibiotics.
10. A method for detecting β-lactam antibiotics, characterized in that, Using the molecularly imprinted electrochemical sensor as described in any one of claims 1-5 includes the following steps: placing the molecularly imprinted electrochemical sensor in the test solution for adsorption, and detecting the current response signal of the sensor using an electrochemical method.
